PENGARUH KAPASITAS FISKAL, EFISIENSI BELANJA, DAN SURPLUS/DEFISIT ANGGARAN TERHADAP KINERJA PEMBAYARAN UTANG PEMERINTAH KABUPATEN/KOTA DI PROVINSI SUMATERA SELATAN - Agista Anggia Irawan; Desi Indriasari; Muhammad Husni Mubarok (LPPM PoliteknikPratamaKendal- Universitas Sains Dan Teknologi Komputer, 2026)
This study aims to obtain empirical evidence on the effect of Fiscal Capacity, Spending Efficiency, and Budget Surplus/Deficit on the Debt Payment Performance of Regency/Municipal Governments in South Sumatra Province. The research method used is descriptive quantitative with multiple linear regression analysis. The population includes 17 regencies/cities over the period 2019–2024, resulting in 85 data samples. Data were collected through documentation studies using audited Local Government Financial Reports (LKPD) accessed from the E-PPID website of the Audit Board of the Republic of Indonesia. The results show that Fiscal Capacity and Budget Surplus/Deficit have a significant positive effect on Debt Payment Performance, while Spending Efficiency has no effect. Simultaneously, all three variables significantly influence the Debt Payment Performance of local governments.